Development and Validation of a Dynamic Nomogram to Predict the Risk of Neonatal White Matter Damage - Cao, Wenjun; Luo, Chenghan; Lei, Mengyuan; Shen, Min; Ding, Wenqian; Wang, Mengmeng; Song, Min; Ge, Jian; Zhang, Qian (Frontiers in Human Neuroscience, 2021)
Purpose: The white matter damage (WMD) was defined as the appearance of rough and uneven echo enhancement in the white matter around the ventricle. The aim of this study was to develop and validate a risk prediction model for neonatal WMD. Materials and Methods: We collected data for 1733 infants hospitalized at the Department of Neonatology at the First Affiliated Hospital of Zhengzhou University from 2017 to 2020. Infants were randomly assigned to training (n=1216) or validation (n=517) cohorts at a ratio of 7:3. Multivariate logistic regression and least absolute shrinkage and selection operator (LASSO) regression analyses were used to establish a risk prediction model and web-based risk calculator based on the training cohort data. The predictive accuracy of the model was verified in the validation cohort. Results: We identified 4 variables as independent risk factors for brain WMD in neonates by multivariate logistic regression and LASSO analysis, including gestational age, fetal distress, prelabour rupture of membranes, and use of cocorticoids. These were used to establish a risk prediction nomogram and web-based calculator (https://caowenjun.shinyapps.io/dynnomapp/). The C-index of the training and validation sets were 0.898 (95% confidence interval: 0.8745–0.9215) and 0.887 (95% confidence interval: 0.8478–0.9262), respectively. Decision tree analysis showed that the model was highly effective in the threshold range of 1%–61%. The sensitivity and specificity of the model were 82.5%, 81.7%, respectively, and the cutoff value was 0.099. Conclusion: This is the first study describing the use of a nomogram and web-based calculator to predict the risk of WMD in neonates. The web-based calculator increases the applicability of the predictive model and is a convenient tool for doctors at primary hospitals and outpatient clinics, family doctors, and even parents to identify high-risk births early on and implementing appropriate interventions while avoiding excessive treatment of low-risk patients. Keywords: neonatal, white matter damage, nomogram, prediction model, perinatal, web-based calculator